Allodemic distribution of plasmids co-harbouring blaCTX-M-15/aac(6′)-Ib-cr/qnrB in Klebsiella pneumoniae is the main source of extended-spectrum β-lactamases in Uruguay's paediatric hospital. (June 2017) - Garcia-Fulgueiras, V.; Araujo, L.; Bado, I.; Cordeiro, N.F.; Mota, M.I.; Laguna, G.; Algorta, G.; Vignoli, R.
Highlights: Extended-spectrum β-lactamases (ESBLs) detected in this study were mainly bla CTX-M family. Klebsiella pneumoniae harbouring bla CTX-M-15 / aac(6′)-Ib -cr/ qnrB showed allodemic behaviour. The array bla CTX-M-15 / aac(6′)-Ib -cr/ qnrB was found in conjugative plasmids, most featuring ccdAB . bla CTX-M-15 accounted for 31.6% of all ESBLs detected in Uruguay's paediatric hospital. Abstract: Objectives: This study aimed to describe the characteristics of clinical isolates of extended-spectrum β-lactamase (ESBL)-producing enterobacteria (EPE) in Uruguay's paediatric hospital. Methods: ESBLs, qnr alleles and aac(6′)-Ib -cr were sought and characterised in EPE isolated between March 2010 and March 2012. Transfer of resistance determinants was assessed by conjugation. Incompatibility (Inc) groups, plasmid toxin–antitoxin systems (TAS) and plasmid size were determined in transconjugants. Clonality was analysed by pulsed-field gel electrophoresis. Multilocus sequence typing was done for ESBL-producing Klebsiella pneumoniae . Results: A total of 77 EPE isolates were characterised, comprising 43% K. pneumoniae, 19.5% Serratia marcescens, 19.5% Escherichia coli, 17% Enterobacter cloacae and 1% Klebsiella oxytoca . ESBLs belonged mainly to the bla CTX-M family (69.6%) [ bla CTX-M-15 (45%) and bla CTX-M-2 (31%)]. The aac(6′)-Ib -cr/ qnrB duplex was the most frequently detected plasmid-mediated quinolone resistance mechanism; this association was detected in K. pneumoniae harbouring bla CTX-M-15 . Transconjugants were obtained for 71% of the EPE. Amongst transconjugants, certain combinations were found between ESBLs and Inc group, e.g. IncA/C– bla CTX-M-2, IncHI1/HI2– bla CTX-M-9 and IncHI1/HI2– bla SHV-12 . In addition, the combination ccdAB–bla CTX-M-15 was also found. K. pneumoniae isolates harbouring bla CTX-M-15 / aac(6′)-Ib -cr/ qnrB showed allodemic behaviour, with a predominance of ST14, ST45 and ST48. Conclusions: In this study, epidemiological changes in ESBL distribution could be explained by the spread of K. pneumoniae harbouring bla CTX-M-15 / aac(6′)-Ib -cr/ qnrB, encoded mainly on conjugative plasmids featuring ccdAB TAS. Since reports of TAS in K. pneumoniae plasmids are scarce, new strategies are needed to combat intrinsic selection pressure exerted by the association, in conjugative plasmids, of resistance mechanisms with TAS.